Challenges facing the growth of kidney transplantation in nigeria: perceptions and knowledge of the nephrologists and other health-care providers (2021)
Objective: The objective of this study was to determine the perception and knowledge of health-care providers to the challenges of sustaining the growth of kidney transplantation programs in Nigeria. Materials and Methods: We conducted a survey of 166 health-care providers. A pretested questionnaire was administered on all participants. Information obtained were demographics, characteristics of end-stage renal disease (ESRD) patients, and prospective kidney donors encountered and perception of the barriers to the growth of kidney transplantation program. Results: The respondents returned 134 questionnaires out of 166 (response rate: 80.7%) and only 121 with complete responses were included in the analysis. The mean age was 42.5 ± 0.8 years and 47.9% were females. A quarter of the health-care providers encountered ESRD patients who were more likely to refuse kidney transplantation and 34.1% reported that most of the prospective kidney donors were unwilling to donate. Most of the health care professionals (71.1%) preferred centers outside Nigeria for their patient’s kidney transplantation, while three leading barriers to the growth of kidney transplantation program reported were lack of patients’ trust (58.8%), failure of inter-program collaborations (55.0%), and absent of governmental supports (48.1%). Conclusions: The health-care professionals reported that more than a third of ESRD patients were not likely to accept kidney transplantation and an equal proportion of prospective donors will not agree to kidney donation. Majority of the health care professionals preferred centers outside Nigeria for patients’ kidney transplantation.